Phenotypic Analysis of Urothelial Exfoliated Cells in Bladder Cancer via Microfluidic Immunoassays: Sialyl-Tn as a Novel Biomarker in Liquid Biopsies - Carvalho, Sandra (2020)
Bladder cancer is the most common malignancy of the urinary tract, having one of the highest recurrence rates and progression from non-muscle to muscle invasive bladder cancer that commonly leads to metastasis. Cystoscopy and urine cytology are the standard procedures for its detection but have limited clinical sensitivity and specificity. Herein, a microfluidic device, the UriChip, was developed for the enrichment of urothelial exfoliated cells from fresh and frozen urine, based on deformability and size, and the cancer-associated glycan Sialyl-Tn explored as a putative bladder cancer urinary biomarker.